2004
DOI: 10.1111/j.1467-842x.2004.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity: Wearing slippers, falls and injury in residential care

Abstract: Background: Risk factor studies for falls in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…The detrimental effect of backless slippers observed in our study is consistent with results by Cho and Lee [33] , who reported that postural sway in older stroke patients was increased when wearing backless slippers or flat shoes compared to being barefoot or wearing high-heel collar shoes, and Ng et al [10] , who found that older stroke patients walked more slowly when wearing slippers compared to walking shoes. These findings are also consistent with previous studies which have identified slippers as a risk factor for falls [12,13] and fall-related injury [14][15][16][17] in older people. There are two possible explanations for this finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The detrimental effect of backless slippers observed in our study is consistent with results by Cho and Lee [33] , who reported that postural sway in older stroke patients was increased when wearing backless slippers or flat shoes compared to being barefoot or wearing high-heel collar shoes, and Ng et al [10] , who found that older stroke patients walked more slowly when wearing slippers compared to walking shoes. These findings are also consistent with previous studies which have identified slippers as a risk factor for falls [12,13] and fall-related injury [14][15][16][17] in older people. There are two possible explanations for this finding.…”
Section: Discussionsupporting
confidence: 93%
“…The most frequently worn indoor footwear is slippers, which often comprise design features considered detrimental to balance, including lack of fixation, thick, soft midsoles, and smooth outsoles [8][9][10][11] . Indeed, several studies have shown that wearing slippers is a risk factor for falls [12,13] and fall-related injury [14][15][16][17] in older people.…”
Section: Introductionmentioning
confidence: 99%
“…Netz, Wu, Becker and Tenenbaum [11] found a relationship with an increase in self-efficacy, which also seems to decrease the fear of falling [12]. Conversely, the fear of falling and the feeling of inadequacy when performing a motor task can accelerate decline, leading the individual into depression [13] or social isolation [14,15]. It seems likely that physical activity presents the elderly with a chance to better master small daily tasks [11], engendering a heightened sense of wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…A representative sample from 14 homes in Auckland in 2000 showed that the average number of medications was 5.6 (SD 3.1), with over 40% of residents receiving some form of psychotropic medication. Half of this group (21% of total) were receiving antidepressant medication and 17% were prescribed antipsychotic drugs (Kerse et al 2004;Kerse 2005). A further population-based survey of long-term care in a different area of New Zealand in 2004 showed similar levels of psychotropic drug use (M. Tucker, Hawkes Bay DHB, personal communication 2005).…”
Section: New Zealand: a Work In Progressmentioning
confidence: 99%